Spontaneous Resolution and Redistribution of Acute Subdural Hematoma : CT and MRI Findings - Yıldırım, Hanefi; Öztürk, Tülin; Esen, Meltem (Fırat University, 2011)
Acute subdural hematoma (ASDH) is a neurosurgical emergency. ASDH is a sequele of trauma with high mortality rate. The true incidence of rapid resolution and redistribution of ASDH is underestimated. Spontaneous resolution and redistribution of acute subdural hematoma is extremely rare and the mechanisms are still unclear. In this study we discussed resolution and redistribution of acute subdural hematoma mechanisms and also review the literature. We show CT and MRI findings of 68 years old male patient with acute subdural hematoma which has been after trauma.

Akut subdural hematom (ASDH) nöroşirurji acillerinden biridir. ASDH yüksek mortalite oranı ile ciddi bir travma sekelidir. ASDH'un hızlı rezolüsyon ve redüstirbüsyonun gerçek insidansı bilinmemektedir. Akut subdural hematomun spontan rezolüsyon ve redüstirbüsyonu nadirdir ve mekanizması henüz anlaşılamamıştır. Bu çalışmayı sunmaktaki amacımız; 68 yaşında erkek hastanın travma sonucu gelişen interhemisferik seviyede subfalsin yerleşimli akut subdural hematomun MR ve BT ile rezolüsyon ve redüstirbüsyonunu literatür ışığında ortaya koymaktır.
Akut Subdural Hematomun Spontan Rezolüsyon ve Redüstirbüsyonu: BT ve MR Bulguları